Parabolaida and Half Tube Baffle Block Performance to Reduce of Length Energy Flow, and Hydraulic Jump on USBR Type II Stilling Basin. - Muhammad, Yogi Prasetyo, Gurawan Djati Wibowo, ST., M.Eng, Jaji Abdurrosyid, ST., MT (2016)
Scouring that occurs downstream of the stilling basin weir respective common. stilling basin scour downstream of the weir will cause damage not only to the base and the river bank, but also can damage the floor of the stilling basin weir, so it could damage the structure of the weir, so the age of the weir is not in compatible with the age of the plan. Stilling basin scouring on downstream is caused by several factors such as the energy flow and the height of the flow rate. The presence of hydraulic jump planned in stilling basin of the weir actually can reduce the flow of energy, but the real reality on the ground is still occur scouring downstream stilling basin. This study determine to know baffle block performance types parabolaida (parabolic three-dimensional) and baffle block half tube to reduce the energy flow of water and reduce the length of hydraulic jump. With presence of the reduction energy flow and the length of hydraulic jump, the water hazard scouring downstream weir can be reduced significantly, so that damage the base and the cliffs of channels (streams) or damage stilling basin weir on stilling basin can be avoided. This research was conducted using the open channel flow flume facility in the Department of Civil Engineering, Faculty of Engineering UMS, the flume length of 10m, width of 60 cm and a maximum discharge of flow of 6000 cm3/s. Ogee spillway weir design using an stilling basin USBR type II and shaped of baffle block design parabolaida and half tubes. Baffle blocks placement in two layers and placed in 3 place on the stilling basin of the weir, at the 1/3 beginning, middle, 1/3 the end of stilling basin of the weir. The discharge that use varies from 3500 cm3/s - 6000 cm3/s (as many as 6 variations of discharge). Baffle blocks performance to reduce the energy and length hydraulic jump of water use the ogee spillway and stilling basin USBR II (without baffle block). From the comparison we can conclude effectively shape of baffle block and baffle blocks placement most optimal to reduce the energy flow water and the length of hydraulic jump.